Faktor-Faktor Penentu yang Mempengaruhi Tarif Sewa dan Harga Jual Ruang Gedung Perkantoran di Jakarta - Simon, Zainal Zawir; Achsani, Noer Azam; Manurung, Adler H.; Sembel, Roy (Universitas Brawijaya, Indonesia, 2015)
This paper empirically examines microeconomic factors that influence rental ratesand selling prices of office space. Quarterly time series data is used for the period of 1996:1to 2012:4. In addition, quantitative methods in the form of vector error correction model(VECM) are also used in this study. The result showed that there is a long term relationshipbetween microeconomic variables with the rental rate and selling price. IRF and FEVDshowed that rental rates and selling prices, in general, responded permanently to the shocksof microeconomic variables. Rental rate is predominantly influenced by rental rate followedby selling price, office space stock, construction cost and vacancy rate. Conversely, sellingprice is predominantly affected by rental rate followed by selling price, office space stock,construction cost and vacancy rate. Investors and developers can use the results of this studyas one of approaches for market analysis, especially office market analysis.